0.2 Ma or 1.2 Ma? Timing of the Linking of the Middle and Lower Reaches of the Yellow River Inferred From Loess‐Palaeosol Sequences. Issue 6 (21st March 2022) - Chen, Qu; Liu, Xiuming; Zhao, Guoyong; Jia, Jia; Ye, Wei; LÜ, Bin; Meadows, Michael; Guan, Jueqi
Abstract: Variations in susceptibility, grain size or accumulation rates of eolian sequences in the Sanmen Gorge entry and exit points and on the Loess Plateau were compared at different time scales. Synchronous changes in multiple proxies occurred during the formation of S14/L14 at different locality. However, the accumulation rates and magnetic properties were different between the sections in S2 or above, implying that there was significant difference in the proximate source for the gorge entry and exit points. It is suggested that the linking of the middle and lower reaches of the Yellow River occurred at around 1.2 Ma (million years ago) after progressively incising the gorge, while the acceleration in loess accumulation at 0.2 Ma can be attributed to its strong incision in the middle reaches and further channelization in the study area. The entrenchment and terrace formation of the river may be associated with tectonic forcing. Plain Language Summary: Ultra‐high loess sedimentation rates around the Sanmen Gorge outlet since the formation of S2 palaeosols (0.24 Ma) has been interpreted as resulting from the drainage of the river through the gorge, while fluvial terraces underlying by S14 palaeosols is expected to yield a time contrast of 1.2 Ma. In this study, we investigate variations in magnetic susceptibility, grain size and accumulation rates of loess‐palaeosol sequences within the gorge and compare these with other local sequences and those from the southern Loess Plateau. Magnetic properties of loess‐palaeosols in the gorge entry and exit points were also compared at different time scales. The results show that synchronous changes in multiple proxies occurred during the S14/L14 formation of loess sections while, in contrast, accumulation rates and magnetic properties of two studied sections at, or above, S2 proved to be distinctly different, implying that there was a different proximal source of loess. It is suggested that the connection of the middle and lower reaches of the Yellow River occurred at around 1.2 Ma, while the acceleration in loess accumulation at 0.2 Ma can be attributed to strong incision in its middle reaches accompanied by further channelization of the river at the study site. Key Points: Concurrent changes in the gorge inlet and outlet indicate the linkage of the middle and lower reaches of the Yellow River at 1.2 Ma Ultra‐high loess sedimentation rates since 0.24 Ma are attributed to strong incision in the middle reaches of the river Rock magnetic investigations suggest a difference in provenance between the loess in the gorge entry and exit points